Single Atom Electrocatalysts: Carbon‐Rich Nonprecious Metal Single Atom Electrocatalysts for CO2 Reduction and Hydrogen Evolution (Small Methods 10/2019). Issue 10 (15th October 2019) - Wang, Tingting; Zhao, Qidong; Fu, Yuanyuan; Lei, Chaojun; Yang, Bin; Li, Zhongjian; Lei, Lecheng; Wu, Gang; Hou, Yang
Abstract : In article number1900210, Bin Yang, Gang Wu, Yang Hou, and co‐workers, review how single atom catalysts have attracted much research attention as promising catalysts in electrocatalytic applications. Various single atom active sites with different nonprecious metals and coordination environments on carbon‐rich materials boost CO2 reduction reaction or hydrogen evolution reaction. Investigation towards structure‐activity relationships lights up the development of new kinds of carbon‐rich nonprecious metals single atom catalysts with electrochemical energy related applications.